2022
DOI: 10.3390/e24030405
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the Balance: A Criticality Perspective

Abstract: Cell populations are often characterised by phenotypic heterogeneity in the form of two distinct subpopulations. We consider a model of tumour cells consisting of two subpopulations: non-cancer promoting (NCP) and cancer-promoting (CP). Under steady state conditions, the model has similarities with a well-known model of population genetics which exhibits a purely noise-induced transition from unimodality to bimodality at a critical value of the noise intensity σ2. The noise is associated with the parameter λ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We now show that the same method, as proposed earlier, can be used in the case of a noiseinduced transition with the starting equation being different (Bose 2022). In the deterministic case, one starts with the steady state equation, 𝐹(𝑥 * ) = 0, obtained from the rate equation, 𝑑𝑥 𝑑𝑡 = 𝐹(𝑥), with 𝑥 * representing the steady states.…”
Section: Box 3 Phase Transitions and Critical Phenomenamentioning
confidence: 85%
“…We now show that the same method, as proposed earlier, can be used in the case of a noiseinduced transition with the starting equation being different (Bose 2022). In the deterministic case, one starts with the steady state equation, 𝐹(𝑥 * ) = 0, obtained from the rate equation, 𝑑𝑥 𝑑𝑡 = 𝐹(𝑥), with 𝑥 * representing the steady states.…”
Section: Box 3 Phase Transitions and Critical Phenomenamentioning
confidence: 85%
“…In our study on the stochastic Solow model, we have demonstrated the existence of two such signatures of an approaching tipping point, A c , which is not a bifurcation point, at which the states of poverty and well-being are evenly balanced but away from which a tilt favouring one or the other regime (economic decline versus economic progress) occurs. The bifurcation point transitions are analogous to equilibrium phase transitions and have been discussed/analysed utilising the criticality perspective [41,44,45]. In economics and the social sciences, opportunities for field experiments are limited, but cross-disciplinary perspectives could facilitate in identifying the universal features, opening up in the process new pathways for exploration.…”
Section: J Stat Mech (2024) 083401mentioning
confidence: 99%
“…According to recent results [34], this means a direct relationship with the reaction of the immune system and variations in the dynamics of the system, either in the time it takes for the populations involved to reach the steady state (we will see it deeply in section 5) and its consequent reduction in the number of cancer cells [35]. Likewise, the variation in the amplitude of the multiplicative noise reflects changes in the microenvironments of the tissues where cancer is generated, and its progression takes place [36].…”
Section: The Effect Of Multiplicative Noise In the Systemmentioning
confidence: 99%